Explicit and Implicit Basic Human Motives, and Public Service Motivation - Slabbinck, Hendrik; Van Witteloostuijn, Arjen (Frontiers in Psychology, 2020)
This article contributes to the literature on the roots of Public Service Motivation (PSM) by turning to the psychological theory of basic human motives. The study explores the differential associations of explicit and implicit basic human motives with PSM, Attraction to Policy-Making (APM), Commitment to the Public Interest (CPI), Compassion (COM), and Self-Sacrifice (SS). Methodologically, the research contributes to the literature by introducing a measurement instrument new to Public Administration: the Brief Implicit Association Test (BIAT). The BIAT is an easy-to-use and flexible tool to probe into the human unconsciousness, offering ample opportunities for further research in Public Administration and Management.